Effect of Roasting Method on Physico-Mechanical and Roasting Characteristics of Chickpea (Cicer arietinum) - Sharanagat, Vijay Singh; Jogihalli, Praveen; Singh, Lochan; Kumar, Kshitiz (Journal of Agricultural Engineering, 2018)
Chickpea grains were roasted by traditional sand roasting (180, 200 and 220ºC) and microwave roasting (450 W, 600 W and 900 W) for 5, 10 and 15 min. The effects of roasting method and their parameters on physico-mechanical and roasting characteristics were determined. Roasting led to an increase in size, sphericity, angle of repose, porosity and puffing index of chickpea. Significant (p<0.05) reduction in fracture force and coefficient of friction was observed. True density decreased with roasting and the lowest value of 787.87 kg.m-3 was observed on sand roasting at 180°C for 15 min. The highest value of puffing index (179.87 %) and length/width ratio (155.04 %) was observed for sand roasting at 220ºC for 15 min and 5 min, respectively. The force required for rupture of chickpea reduced with roasting, and the lowest value (32.28 N) was observed during sand roasting at 220ºC for 10 min. The optimum roasting condition identified for sand and microwave roasting to obtain higher puffing index, lower hardness and rupture energy was observed to be 220 ºC for 10 min and 600 W for 15 min, respectively.